2022
DOI: 10.35381/racji.v7i1.1702
|View full text |Cite
|
Sign up to set email alerts
|

Gamification strategies and speaking fluency in EFL elementary students

Abstract: Students in public schools from Ecuador have problems regarding speaking fluency due to the poor development of EFL teaching strategies and motivation issues. Students need constant teacher input, which provokes demotivation and low academic results. Gamification based on connectivism, constructivism, PPP methods, and communicative focus was used to solve and correct class deficiencies. In this context, this article has as objective to analyze the effect of gamification strategies in improving speaking fluency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For example, Akbar (2014) and Zhang (2009) are convinced that encouraging students to read extensively to build their vocabularies will help them gain confidence in speaking. Of course, work being done with gamification could provide these students with the expansive vocabulary they may need to become confident speakers (Reinhardt & Sykes, 2014;Guapisaca & Argudo-Garzón, 2022;Carmona-Chica & Argudo-Garzón, 2022;Marin-Pacurucu & Argudo-Garzón, 2022;Kukulsa-Hulme & Shield, 2008, & Taraghat & Khodabakhsh 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Akbar (2014) and Zhang (2009) are convinced that encouraging students to read extensively to build their vocabularies will help them gain confidence in speaking. Of course, work being done with gamification could provide these students with the expansive vocabulary they may need to become confident speakers (Reinhardt & Sykes, 2014;Guapisaca & Argudo-Garzón, 2022;Carmona-Chica & Argudo-Garzón, 2022;Marin-Pacurucu & Argudo-Garzón, 2022;Kukulsa-Hulme & Shield, 2008, & Taraghat & Khodabakhsh 2016.…”
Section: Discussionmentioning
confidence: 99%
“…They developed three categories that they believe merit further research: 1. game-enhanced language acquisition that can utilize commercial off-the-shelf (COTS) games in the classroom; 2. the use of games to enhance language learning means games that are specifically designed for educational purposes, and 3. gameinformed teaching is limited to the use of game and play principles in the language classroom. Researchers in Ecuador have developed several game elements for the language classroom (Fajardo-Guapisaca & Argudo-Garzón, 2022;Carmona-Chica & Argudo-Garzón, 2022;Marin-Pacurucu,& Argudo-Garzón, 2022). Game-based programs explicitly designed for vocabulary enhancement show potential for aiding students with speaking anxiety.…”
Section: Gamificationmentioning
confidence: 99%
“…Teachers' attitudes, perceived usefulness, and perceived social influences can predict their intentions to use gamification in EFL classrooms (Asiri, 2019). Furthermore, gamification can be employed to improve speaking fluency in EFL students at elementary schools (Marin-Pacurucu & Garzón, 2022) and reinforce learners' physical, mental, and emotional aspects in memorizing and classifying language forms (Mila & Mahbub, 2022). However, there is still inadequate research on the benefits of gamification for acquiring English as a Foreign Language (EFL) (Ivanjko, Pavlina, & Grubješić, 2020).…”
Section: Gamification In the Efl Contextmentioning
confidence: 99%
“…Moreover, Figueroa (2015) revealed that gamification strategies can help to progress the learning of writing, reading, and speaking skills while motivating collaboration and interaction. For instance, many studies have found that gamification improves speaking skills since it encourages students' participation, and they are more motivated to practice using games (Asih and Halisiana, 2022;Putra, 2020;Marin-Pacurucu and Argudo-Garzón, 2022). As a result, this research aimed to identify the effectiveness of gamification through technology in the development of English-speaking skills.…”
Section: Introductionmentioning
confidence: 99%